Comparative study of the anticoagulation activity of combined solutions of dihydroquercetin with hyaluronic acid - Semenova, Kseniia; Nosalska, Tetyana (Annals of Mechnikov’s Institute, 2023)
Introduction. The need for cosmetology procedures grows every year, especially for injection and hardware techniques. In aesthetic correction, among minimally invasive procedures, contour plastic ranks second in popularity after botulinum therapy. One of the most frequent phenomena after injection procedures, which usually do not pose a significant threat, but are aesthetically undesirable, is hemorrhage into soft tissues. Various means are used to eliminate resorption and fading of hematomas: creams, lotions, ointments, etc. Taking into account the literature data on the properties of hyaluronic acid (HA) and a powerful natural antioxidant - the bioflavonoid dihydroquercetin (DHA), we conducted a study on the creation of an injectable drug based on them for a quick effect on subcutaneous hematomas. Materials and methods. The study was carried out in vitro according to the Moravyts method. The object of the study were samples of injection solutions of DHA with HA: - DHA with PVP (Povidone K-17) 5%, pH 7.28; - DHA with HA and L-arginine, pH 7.42. Up to 2 drops of rat blood (approximately 0.1 ml) were applied to the hour glass, no substances were added (intact control), 0.05 ml of physiological solution was added to the blood (control No. 2), 0.05 ml of DHA was added to the blood (experiment 1), 0.05 ml of DHA with HA and L-arginine was added to the blood (experiment 2). The time of coagulation was determined from the moment of the appearance of the first fibrin threads stretching behind the needle. Results and discussion. As a result of the conducted research, it was established that the blood clotting time (intact control) in the absence of its contact with any substance was an average of 3.63 seconds. Addition of saline solution to blood by 35% increased blood clotting time, possibly due to its dilution. Addition of DHA solution with 5% PVP significantly increased blood clotting time by 40.36% compared to saline and almost 2 times compared to the intact control. When adding a DHA solution with HA and L-arginine to the blood, the coagulation time increased significantly - 2.7 times compared to that when adding a physiological solution and 2 times - compared to a DHA solution with 5% PVP. Conclusion. An in vitro comparative study of the anticoagulation activity of combined solutions showed that the combined solution (DHA, HA L-arginine) has the most pronounced effect on hemostasis. The conducted studies are important for the further study of the properties of the composition based on dihydroquercetin, hyaluronic acid and L-arginine.